PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP PRODUKTIVITS KERJA KARYAWAN PT. BANK CENTRAL ASIA KCU KALIMALANG - Nabila Putri Fachrianda; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
Purpose to determine the effect of education and training on the work productivity employees at PT. BCA KCU Kalimalang. This research is included in the category of causal associative research using a quantitative approach. The sampling technique used a saturated sample. The research method uses simultaneous and partially linear regression analysis. The results of the study indicate that in simultaneous or partially ways, education and training had a positive and significant effect on the work productivity employees at PT. BCA KCU Kalimalang.